ANALISIS TEAMWORK DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. KINANTI UTAMA KARYA - Faizal Ridwan Zamzany; Edi Setiawan; Desy Permatasari (Journal of Islamic Economy and Business (JIsEB), 2021)
This study aims to see the influence between teamwork and organizational culture on employee performance at PT Kinanti Utama Karya. The technical analysis of the data used is multiple linear analysis. The results of this study indicate that teamwork and organizational culture variables simultaneously affect employee performance. Partially the teamwork variable has a positive and significant effect on employee performance. The results of this study indicate that the better the teamwork, the better the employee's performance. Furthermore, partially organizational culture has a positive and significant effect on employee performance. The results showed that organizational culture is a factor that has a strong influence on employee performance in the company.